Pengaruh Penerapan Good Governance, Pemahaman Standar Akuntansi Pemerintahan terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Karawang - Jennifer Carolina Golung,; R. Budi Hendaris, (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The quality of local government financial reports is a key indicator of the accountability of public financial management. Although the Karawang Regency Government routinely receives an Unqualified Opinion (WTP), this opinion is often accompanied by an Explanatory Paragraph (WTP-DPP), which indicates significant audit findings from the Supreme Audit Agency (BPK). These audit findings indicate that there are still inconsistencies in good governance practices and weaknesses in understanding Government Accounting Standards (SAP). This study aims to analyse the influence of the implementation of good governance and understanding of Government Accounting Standards (SAP) on the quality of financial reports in the Karawang Regency Government. The research method used is quantitative research. The data was collected through a questionnaire. The target population consists of 22 Local Government Agencies (OPD) with a sample size of 44 respondents. The sampling approach used is saturated sampling. Data analysis was conducted using IBM SPSS version 27. The results of the analysis indicate that the implementation of good governance has a significant partial effect on the quality of financial reports. Similarly, understanding of Government Accounting Standards has a significant partial effect on the quality of financial reports. Simultaneously, these two variables contribute 62.8% to the quality of financial statements, while the remaining 37.2% is influenced by other factors not explained in this study.